Fizicheskaja rabotosposobnost' i osobennosti mobilizacii jenergeticheskih mehanizmov pri nagruzkah u kvalificirovannyh sportsmenov raznoj specializacii - Lysenko, E.; Stankevich, L.; Gatilova, G. (Science in Olympic Sport, 2013)
Objective. To analyze the features of energy production in athletes, specializing in various competitive disciplines under physical loads of different intensity and duration. Methods. The study involved 54 qualified athletes specializing in the 100, 800 and 5000 m race. The maximum intensity loads of 15 s (Wmax15s) and 60 s (Wmax60s) duration were used to estimate the anaerobic capacity of athletes. Results. For sprinters, a negative correlation was revealed between the blood lactate concentration and intensity of loads r = -0.68 for Wmax15s and r = -0.76 for Wmax60s. While for 800 m runners direct relationship was found between blood lactate concentration and load intensity r = 0.81 for Wmax15s and r = 0.89 for Wmax60s. Moreover, stayers demonstrate positive correlation between the level of blood lactate and intensity of loads for Wmax15s r = 0.59 and negative correlation for Wmax60s r = -0.79. Conclusions. Characteristics of qualified athletes` performance by load intensity under different modes of its execution differ in relation to duration of the main race distance and changes in activity of functional systems providing athlete`s performance.